A pattern of antimicrobial susceptibility and the correlation of cotrimoxazole and fluoroquinolones in Escherichia coli resistant uropathogens in Ibn-Sena hospital in Benghazi- Libya. - Gargoum , Huda M.; Elsieah , Zinab M; Moftah , Moftah M.; Eljaroshi , Mokhtar O. (Libyan Journal of Science &Technology, 2025)
Uncontrollable use of antibiotics to treat uropathogens is one of the major causes of increasing antimicrobial-resistant Escherichia coli (E. coli) strains. Therefore the choice of antibiotic therapy is needed to be based on their antibiotic susceptibility tests. We investigated the prevalence and antibiotic susceptibility of E. coli in uncomplicated urinary tract infection (UTI) in 1011 samples during 8 months period in Ibn-Sena clinic in Benghazi. The E. coli was the most isolated uropathogen (64%). The most resistant antibiotic to this uropathogen was amoxicillin (51.6%), followed by cotrimoxazole (47.7%) and the percentage of ciprofloxacin was 26.6%. When the utilization of ciprofloxacin increased lately as an alternative to cotrimoxazole, its resistance increased and we found that this increase was positively correlated with cotrimoxazole. In conclusion, monitoring and investigating antibiotic-sensitivity patterns may help the physician to prepare reliable strategies for better management and control of E. coli infections.